2014
DOI: 10.1080/08985626.2014.918183
|View full text |Cite
|
Sign up to set email alerts
|

The communal roots of entrepreneurial–technological growth – social fragmentation and stagnation: reflection on Atlanta's technology cluster

Abstract: Why do some entrepreneurial high-technology industrial clusters grow and prosper, while others stagnate? Even after several decades of research, we have yet to find a definitive answer. One of the main debates in the literature revolves around the importance of societal variables, such as the growth of a cohesive community, versus the importance of factor availability, such as the supply of highly educated labour. Employing a critical case study design to analyse the technology industry in metropolitan Atlanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 69 publications
0
31
0
1
Order By: Relevance
“…The state of St. Louis during this time was similar to Atlanta, Georgia, as described by Breznitz and Taylor (2014) -there were some entrepreneurs, a few entrepreneurial resources, including venture capital, but the social structures needed to create a vibrant community were absent. There were a few disconnected entrepreneurial support organizations which appeared in the 2000s, including CORTEX (a technology district), the Coalition for plant and Life Sciences (later renamed BioSTL, a leader in spearheading the infrastructure needed for bioscience entrepreneurship) and Innovate VMS (a mentoring service modelled after Venture Mentoring Service at MIT).…”
Section: Background Of St Louis and The Arch Grantsmentioning
confidence: 93%
“…The state of St. Louis during this time was similar to Atlanta, Georgia, as described by Breznitz and Taylor (2014) -there were some entrepreneurs, a few entrepreneurial resources, including venture capital, but the social structures needed to create a vibrant community were absent. There were a few disconnected entrepreneurial support organizations which appeared in the 2000s, including CORTEX (a technology district), the Coalition for plant and Life Sciences (later renamed BioSTL, a leader in spearheading the infrastructure needed for bioscience entrepreneurship) and Innovate VMS (a mentoring service modelled after Venture Mentoring Service at MIT).…”
Section: Background Of St Louis and The Arch Grantsmentioning
confidence: 93%
“…Ecosystem components create an environment that assists entrepreneurs and increases the likelihood of venture success (Roundy & Fayard, ). However, the mere presence of EE components is not indicative of a vibrant ecosystem (Breznitz & Taylor, ). An additional characteristic—ecosystem leadership—is needed to coordinate EE components (e.g., Colombo et al, ; Cunningham et al, ; Harper‐Anderson, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Mack and Mayer () argued that the lack of EE leadership working together suggested that the ecosystem needed more coordinated efforts. Similarly, in a study of the Atlanta, USA, EE, Breznitz and Taylor () found that social fragmentation, the opposite of coordination, was an obstacle to growth in the city's ecosystem and that EE leadership should strive to promote learning, information sharing, access to resources, and community building.…”
Section: Introductionmentioning
confidence: 99%
“…Nesse sentido, para disseminar uma cultura inovadora, a conectividade é essencial e a interação entre os atores pode ser um parâmetro de medição do grau de desenvolvimento de um ecossistema (STEPHENSON, 2008). Para Breznitz (2014), os diversos ecossistemas que se desenvolveram ao redor do mundo, passaram pelas mesmas fases de desenvolvimento e podem ser classificados como nascentes, em evolução, maduro, autossustentável. Research, Society and Development, v. 9, n. 3, e143932536, 2020 (CC BY 4.0 Quadro 1 -Níveis ou estágio de Maturidade Research, Society and Development, v. 9, n. 3, e143932536, 2020 (CC BY 4.…”
Section: Metodologias Para Diagnóstico De Ecossistemasunclassified